Post-mastectomy radiation therapy without usage of a bolus may be a reasonable option. (23rd January 2017) - Nakamura, Naoki; Arahira, Satoko; Zenda, Sadamoto; Yoneyama, Kimiyasu; Mukai, Hirofumi; Onozawa, Masakatsu; Toshima, Masamichi; Motegi, Atsushi; Hirano, Yasuhiro; Hojo, Hidehiro; Kibe, Yuichi; Akimoto, Tetsuo
Abstract: To clarify the efficacy and toxicity of post-mastectomy radiation therapy (PMRT) without usage of a bolus, we identified 129 consecutive patients who received PMRT at the National Cancer Center Hospital East between 2003 and 2012. Seven of the 129 patients who received breast reconstruction before PMRT were excluded. All patients received PMRT of 6 MV photons, without usage of a bolus. The median follow-up duration for all eligible patients was 47.7 months (range: 4.0–123.2). Local, locoregional and isolated locoregional recurrence was found in 12 (9.8%), 14 (11%) and 5 patients (4.1%), respectively. The 3- and 5-year cumulative incidence of local recurrence, locoregional recurrence and isolated locoregional recurrence was 9.2 and 10.7%, 10.8 and 12.4%, and 4.3 and 4.3%, respectively. Although Grade 2 dermatitis was found in 11 patients (9.0%), no Grade 3–4 dermatitis was found. On univariate analysis, only a non-luminal subtype was a significant predictor for local recurrence ( P < 0.001). On multivariate analysis, a non-luminal subtype remained as an independent predictor for local recurrence ( P = 0.003, odds ratio: 10.9, 95% confidence interval: 2.23–53.1). In conclusion, PMRT without usage of a bolus resulted in a low rate of severe acute dermatitis without an apparent increase in local recurrence. PMRT without usage of a bolus may be reasonable, especially for patients with a luminal subtype.